The Levy Economics Institute working paper collection - Jerome Levy Economics Institute (New York : The Levy Economics Institute of Bard College, 1986)
Working papers present research in progress by Levy Institute scholars and conference participants. The purpose of the series is to disseminate ideas to, and elicit comments from academics and professionals.
Title from disc label
System requirements: Adobe Reader software required and included compliments of Adobe System, Inc. and autorun-enabled for PC.
Keywords: Economics -- Periodicals; Economics -- Research